PENERAPAN METODE GAME BASED LEARNING SEBAGAI MEDIA PEMBELAJARAN SISWA KELAS 5 DI SDN 1 IMOGIRI - Cindy Nur'aini Wulandari; Isyara Mabda Kirana; Lovandri Dwanda Putra; Meutya Devi Arumsari; Najwa Sulthania (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning in elementary schools requires the use of teaching methods that can enhance students’ activeness, motivation, and understanding of learning materials. One method considered effective in addressing these needs is Game-Based Learning (GBL), a learning approach that utilizes games as instructional media to achieve learning objectives. This study aims to describe the implementation of the Game-Based Learning method as a learning medium and to analyze its impact on the activeness and learning outcomes of fifth-grade students at SDN 1 Imogiri. This research employs a qualitative approach using a case study design. The research subjects consist of fifth-grade students and a classroom teacher, while the research object is the implementation of Game-Based Learning in the learning process. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the implementation of Game-Based Learning increases students’ learning motivation, encourages active participation in learning activities, and helps students better understand the learning materials. The learning atmosphere becomes more enjoyable, interactive, and less monotonous, leading to higher student enthusiasm during the learning process. Therefore, Game-Based Learning is proven to be an effective, innovative, and enjoyable alternative learning medium for elementary school students.